You are on page 1of 10

()

() ,


.

d (M,E) = d (M,)

,

:
'
p
p
: ( ,0)
: x = y 2 = 2px
2
2
p : | p | = d ( E , )

B : yy
'
p
p
: (0 , )
: y = x 2 = 2py
2
2
p : | p | = d ( E , )


.
c1 : y 2 = 2px (x,y) (

y2
, y)
2p

c1 : y 2 = 2px , y2 0 2px 0
p > 0 x 0 , p < 0 x 0 ,


xx' ( ) c1 : y 2 = 2px
( x1, y1)c1 M1(x1, -y1)c1 . (-y1)2 =y12 = 2px1
yy' ( ) c2 : x 2 = 2py
( x1, y1)c2 M1( - x1, y1)c2 . (-x1)2 =x12 = 2py1

( x0 , y0 ) y2 = 2px , ,

d ( M , E ) =| x 0 +

p
|
2


c1 : y 2 = 2px (x1,y1) .

p
:
yy1 = p ( x+x1 ) =
y1
2
c2 : x = 2py (x1,y1) .

x
:
xx1 = p ( y+y1 ) = 1
p
y = +
y = x+k c1 2

y = 2 px
( x+)2 =2px ,
p =2k

1(x1 ,y1)
1 1t
1(x1 ,y1) xx' ( -x1 , 0)
y12 = 2px1 y22 = 2px2 y 22 y12 = 2p(x2-x1)
2p
( y2 y1 )(y2+y1) = 2p(x2-x1) 1 2 =
1 + 2
1(x1 ,y1) ,
2(x2 ,y2) M(x0,y0 ) 12
y y0 = p (x+x0 )
H 12 1(x1 ,y1) , 2(x2 ,y2)

p2
y1y2 = - p2
x1x2 =
4
1, 2

, ' ( ) , '

, ' ( = 2)
' ( =2 = )

C d(M,E)+d(M ,E') = 2 > 2 = d(E,E')


>

xx '

yy'

xx ' ' yy'


' :

yy ' ' xx'


' :

' (-,0)
(,0)
= 2

' (0 , -) , (0, )
= 2

x2
a

y2

=1

2 = 2 +2 , = 2 2

>

x2
2

y2
2

=1

2 = 2 +2 , = 2 2

>

( )
.
= =0 x2+y2 = 2

xx' yy' .
1(x1 , y1) c 2( - x1 , y1) , 3( -x1 , - y1) , 4 (x1 , - y1) c

= 1 . y = 0 x = x=0 y = . '
a 2 2
c ' '( -,0) , (,0) ' '( -,0)
(,0) .
c :

x2

y2

' =2 ' = 2
.

(1 , 3)
2 (13) 2

x2
2

y2
2

= 1

x2
2

=1

y2
2

1 x2 2 |x| - x

- y , c , ,
x = , y =
.

< 1 .

2 2
2 2
2

=
2=
=
1

(
) = 1 2 .
2

o 1
0

o 0

o ,

x2

y2

= 1 (x1,y1)
a 2 2
.
xx1

a2

yy1
2

x2

=1

y2

+
= 1 (x1,y1)
2 2
.
xx1

yy1

2
2

=1


' , '

, ' ( ) , '

, ' ( = 2)
' ( =2 = )
C | d(M,E)-d(M ,E') | = 2 < 2 = d(E,E')
>

xx '

yy'

xx ' ' yy'


' :

yy ' ' xx'


' :

' (-,0)
(,0)
= 2

' (0 , -) , (0, )
= 2

x2 y 2

=1
a2 2

2 = 2 +2 , = 2 2

>

y2

x2

=1

2 = 2 +2 , = 2 2

>

.
1
=
x2 y2 = 2 y2 x2 = 2

xx' yy' .
1(x1 , y1) c 2( - x1 , y1) , 3( -x1 , - y1) , 4 (x1 , - y1) c

x2 y 2

= 1 . y = 0 x = ' c '
a2 2
'( -,0) , (,0).
x = 0 yy

c :

x2 y 2
x2
y2

=
1

=
1
+
1 x2 2 |x| x x -
2
2
2
2
a
a

c , ,
x = , 2 .

y= x
a

y =

x y = -

x2 y 2

= 1
a2 2

: (x,y) x

0
y =

y= x
a

x y = -

y2

x2

=1

x2 y 2
x2 y 2

=
1

= 0
a2 2
a2 2

y ,

y2

x2

= 1

y2

x2

=0

x=a
(,)

(,0) (,0)

y= x
a
( -,- ) ( ,- ) ( , ) (- , )
x2 y 2
2 2 = 1
a

y2

x2

= 1


( -,- ) ( ,- ) ( , ) (- , )
=

> 1 .

2 + 2
2 + 2

= 1 + ( )2 = 2 1 .
2=
=
2

0 ,

= 2
=


x2 y 2

= 1
a2 2
(x1,y1) .

xx1 yy1
2 =1
a2

y2

x2

= 1 (x1,y1) .


yy1

xx1

=1

'
, '